2011
DOI: 10.2337/db10-1707
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase 4 Is a Novel Adipokine Potentially Linking Obesity to the Metabolic Syndrome

Abstract: OBJECTIVEComprehensive proteomic profiling of the human adipocyte secretome identified dipeptidyl peptidase 4 (DPP4) as a novel adipokine. This study assessed the functional implications of the adipokine DPP4 and its association to the metabolic syndrome.RESEARCH DESIGN AND METHODSHuman adipocytes and skeletal and smooth muscle cells were used to monitor DPP4 release and assess the effects of soluble DPP4 on insulin signaling. In lean and obese subjects, depot-specific expression of DPP4 and its release from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
565
3
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 529 publications
(614 citation statements)
references
References 33 publications
32
565
3
14
Order By: Relevance
“…The correlations between DPP4 activity and BMI (r = 0.24, p = 0.0017) and total cholesterol (r = 0.27, p = 0.0006) remained significant after adjusting for age and sex (Table 3), but not found to increase [9,10] and decrease [11][12][13] in patients with type-2 diabetes. Moreover, it has been reported that the degree of plasma DPP4 activity was significantly higher in obese subjects than in lean subjects [14,15]; however, the DPP4 hyperactivity in obese individuals did not seem to be affected by their degree of overweightedness [14]. Moreover, it has been reported that the degree of plasma DPP4 activity was affected by widely used anti-diabetic agents, such as metformin [16], and ageing [12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlations between DPP4 activity and BMI (r = 0.24, p = 0.0017) and total cholesterol (r = 0.27, p = 0.0006) remained significant after adjusting for age and sex (Table 3), but not found to increase [9,10] and decrease [11][12][13] in patients with type-2 diabetes. Moreover, it has been reported that the degree of plasma DPP4 activity was significantly higher in obese subjects than in lean subjects [14,15]; however, the DPP4 hyperactivity in obese individuals did not seem to be affected by their degree of overweightedness [14]. Moreover, it has been reported that the degree of plasma DPP4 activity was affected by widely used anti-diabetic agents, such as metformin [16], and ageing [12].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Lamers et al reported that DPP4 is an adipokine that might be linked to obesity, and the serum DPP4 concentration is correlated with various clinical parameters such as age; BMI; the sizes of subcutaneous and visceral adipocytes; and the levels of insulin, adiponectin, and leptin in lean (n = 20) and morbidly obese (n =20) men [15]. Our data are consistent with those of previous studies and support the evidence obtained from obese and healthy young subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In animal and cell culture studies adiponectin increased the bioavailability of NO directly, stimulating eNOS, and indirectly, by reducing the concentration of superoxide products (27)(28)(29). Sharma et al (2008) The results of recent experimental studies suggest an increased expression of DPP-4 in adipocytes of visceral fat and increased serum enzymes in patients with IR and T2DM (39,40). In vitro studies also suggest a possible link between DPP4 activity and renovascular protective effect (41,42).…”
Section: Evaluation Of the Hypothesismentioning
confidence: 95%
“…However, the expression levels were not different among the control, OVX-HF, and Tene groups (Supplemental Figure 1, see section on supplementary data given at the end of this article). Since the secretion of DPP4 was more prominent in patients with metabolic syndrome than simple obese subjects (Lamers et al 2011), other metabolic factors might influence the secretion.…”
Section: Dpp4 Inhibitors Represent a Relatively New Class Of Antidiabmentioning
confidence: 99%
“…Recently, DPP4 has been shown to be secreted from adipose tissue in a tissue-volume-dependent manner, and serum DPP4 concentrations were positively correlated with an increased BMI, fat volume, and insulin concentration in humans (Lamers et al 2011). Because visceral fat accumulation is a notable phenotype of postmenopause, we measured the expression of DPP4 in the perigonadal fat of the mice.…”
Section: Dpp4 Inhibitors Represent a Relatively New Class Of Antidiabmentioning
confidence: 99%